2022
DOI: 10.1073/pnas.2204536119
|View full text |Cite
|
Sign up to set email alerts
|

Friction-driven membrane scission by the human ESCRT-III proteins CHMP1B and IST1

Abstract: The endosomal sorting complexes required for transport (ESCRT) system is an ancient and ubiquitous membrane scission machinery that catalyzes the budding and scission of membranes. ESCRT-mediated scission events, exemplified by those involved in the budding of HIV-1, are usually directed away from the cytosol (“reverse topology”), but they can also be directed toward the cytosol (“normal topology”). The ESCRT-III subunits CHMP1B and IST1 can coat and constrict positively curved membrane tubes, suggesting that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 77 publications
4
20
0
Order By: Relevance
“…The dots indicate the position of the proteins with respect to the membrane and colours correspond to the protein names listed. The membrane remodelling activity of all these proteins has been confirmed by previous in vitro reconstitutions 15,29,3437 , while the scission activity of bacterial DynA is established here. (b) Schematics representing membrane fusion via a hemi-fusion intermediate with DynA (in green) reconstituted on the outer leaflet.…”
Section: Discussionsupporting
confidence: 80%
“…The dots indicate the position of the proteins with respect to the membrane and colours correspond to the protein names listed. The membrane remodelling activity of all these proteins has been confirmed by previous in vitro reconstitutions 15,29,3437 , while the scission activity of bacterial DynA is established here. (b) Schematics representing membrane fusion via a hemi-fusion intermediate with DynA (in green) reconstituted on the outer leaflet.…”
Section: Discussionsupporting
confidence: 80%
“…Although the precise mechanism by which ESCRT-III proteins and Vps4 remodel and cut membranes remains an unresolved question in the field, purified ESCRT-III proteins have been shown to form composite polymers that assume a wide variety of forms, from flat spirals, to cones and helices (7)(8)(9)(10)(11)(12). In addition, reconstitution experiments have shown that ESCRT-III copolymers can undergo stepwise changes in their composition in the presence of ATP and Vps4, which can drive changes in membrane curvature that lead to membrane tube formation and, ultimately, membrane scission (13)(14)(15)(16)(17). Furthermore, physical computational models of the process show that sequential changes in polymer structure are likely sufficient to drive membrane remodelling and scission (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…To reproduce the unbinding sequence observed in experiment, we find that our filament rigidity needs to be between 3 and 7-fold larger than previous estimates [13, 25]. This apparent mismatch is due to the fact is that our passive model does not account for active energy supply, while in experiments dynamic disassembly is only observed upon addition of ATPase Vps4, which unfolds monomers and extracts them from the filament [9, 10, 2731]. This led us to explore whether a Vps4-like activity that promotes stress-dependent polymer disassembly could aid the process.…”
Section: Role Of Activitymentioning
confidence: 88%